2021
DOI: 10.7554/elife.70818
|View full text |Cite
|
Sign up to set email alerts
|

Astrocyte GluN2C NMDA receptors control basal synaptic strengths of hippocampal CA1 pyramidal neurons in the stratum radiatum

Abstract: Experience-dependent plasticity is a key feature of brain synapses for which neuronal N-Methyl-D-Aspartate receptors (NMDARs) play a major role, from developmental circuit refinement to learning and memory. Astrocytes also express NMDARs although their exact function has remained controversial. Here we identify in mouse hippocampus, a circuit function for GluN2C NMDAR, a subtype highly expressed in astrocytes, in layer-specific tuning of synaptic strengths in CA1 pyramidal neurons. Interfering with astrocyte N… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 123 publications
(210 reference statements)
1
16
0
Order By: Relevance
“…NMDAR subunit expression varies between neuronal types and during development thus providing of means of adapting the NMDAR-mediated component of excitatory postsynaptic potentials (EPSPs) to the physiological context. Principal neurons account for the majority of neurons in the adult forebrain, where they predominantly express GluN2A and 2B, and to a much lesser extent GluN2C or D 20 22 . While GluN2B predominates at birth and continues to make a major contribution to synaptic NMDARs into adulthood, GluN2A is upregulated during early postnatal development 20 , 23 26 , by neuronal activity 27 29 and sensory experience 30 33 , and accounts for much of the observed developmental speeding of NMDAR-mediated excitatory postsynaptic currents (NMDA-EPSCs) 23 , 24 .…”
Section: Introductionmentioning
confidence: 99%
“…NMDAR subunit expression varies between neuronal types and during development thus providing of means of adapting the NMDAR-mediated component of excitatory postsynaptic potentials (EPSPs) to the physiological context. Principal neurons account for the majority of neurons in the adult forebrain, where they predominantly express GluN2A and 2B, and to a much lesser extent GluN2C or D 20 22 . While GluN2B predominates at birth and continues to make a major contribution to synaptic NMDARs into adulthood, GluN2A is upregulated during early postnatal development 20 , 23 26 , by neuronal activity 27 29 and sensory experience 30 33 , and accounts for much of the observed developmental speeding of NMDAR-mediated excitatory postsynaptic currents (NMDA-EPSCs) 23 , 24 .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, reduced recruitment of low-responsive cells following astrocyte Grin1 KD could be indicative of decreased plasticity 48 . Both astrocyte Ca 2+ signaling and astrocyte NMDARs have been linked to plasticity, since IP 3 R2 knockout mice have diminished cortical homeostatic plasticity 81 and hippocampal astrocyte NMDARs mediate heterosynaptic plasticity 27,82 . Therefore, a reduction in cortical astrocyte NMDARs and Ca 2+ MDs following our Grin1 KD approach may have effects on cortical plasticity, but further experiments are required to determine the influence of these pathways on this type of neuronal regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, reduced recruitment of low-responsive cells following astrocyte Grin1 KD could be indicative of decreased plasticity 48 . Both astrocyte Ca 2+ signaling and astrocyte NMDARs have been linked to plasticity, since IP3R2 knockout mice have diminished cortical homeostatic plasticity 81 and hippocampal astrocyte NMDARs mediate heterosynaptic plasticity 27,82 .…”
Section: Cortical Circuit Regulation and Sparse Sensory Codingmentioning
confidence: 99%
“…Analysis of these synaptically localized transcripts reveal diverse modes of regulation of synaptic function in the pathogenesis of AD [ 18 ]. Among these example genes, a deeper investigation reported that the differentially localized and expressed mRNA levels of Grin2c could potentially link the regulation of synaptic strength distribution to the expression of synaptic plasticity [ 19 ].…”
Section: Introductionmentioning
confidence: 99%